2009
DOI: 10.1016/j.aop.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Anyonic order parameters for discrete gauge theories on the lattice

Abstract: We present a new family of gauge invariant non-local order parameters ∆ A α for (non-abelian) discrete gauge theories on a Euclidean lattice, which are in one-to-one correspondence with the excitation spectrum that follows from the representation theory of the quantum double D(H) of the finite group H. These combine magnetic flux-sector labeled by a conjugacy class with an electric representation of the centralizer subgroup that commutes with the flux. In particular cases like the trivial class for magnetic fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In ordinary lattice gauge theories [34][35][36][37] the field algebra is link-based. This framework has also been used in studies of Chern-Simons gauge theories on the lattice [14,[38][39][40][41][42]. In our lattice formulation of a doubled Chern-Simons gauge theories, on the other hand, the field algebra is cross-based.…”
Section: Introductionmentioning
confidence: 99%
“…In ordinary lattice gauge theories [34][35][36][37] the field algebra is link-based. This framework has also been used in studies of Chern-Simons gauge theories on the lattice [14,[38][39][40][41][42]. In our lattice formulation of a doubled Chern-Simons gauge theories, on the other hand, the field algebra is cross-based.…”
Section: Introductionmentioning
confidence: 99%
“…[3] requires one to have access to an infinite set of ground-states labeled by a continuous parameter, and is difficult to implement. Recently, Bais et al [20] also discussed extracting S matrix in numerical simulations, by explicit braiding of excitations. In contrast, here we will just use the set of ground states on a torus, to determine the braiding and fusing of gapped excitations.…”
mentioning
confidence: 99%
“…Once the condensate is identified, we have shown how to unambiguously reconstruct the S-matrix of the low-energy theory in a broken or unbroken phase by measurements of the complete set of braided loop operators, using the anyonic loop operators we proposed in the earlier work [16]. Due to an auxiliary gauge symmetry these operators are particularly well suited for detecting the nontrivial splittings of fields that correspond to fixed points under fusion with the condensate.…”
Section: Discussionmentioning
confidence: 99%
“…We return to D(H ) and its representations in section 2.2. An important consequence of this underlying symmetry is that it suggested that in the pure DGT a corresponding set of gauge invariant loop operators should exist, thereby generalizing the Wilson/'t Hooft operators to all anyonic species, and indeed such operators have been constructed [16]. With these operators in hand, one can now probe the full phase structure of discrete gauge theories in a lattice formulation and that is what will be done in this paper.…”
Section: Introductionmentioning
confidence: 91%